Thermal performance analysis of solar thermal system integrated with phase change material / Foad Nasouri - Foad, Nasouri (2013)
The concern of this study is to investigate two systems of cylindrical parabolic collector based on first thermodynamic law in one dimensional space. The different between these two systems which has been considered is that the second system is a cylindrical parabolic collector like the first one, but some changes are taken place in its absorber in order to create and design a space to install phase change material. First system is studied under steady state and second one under the unsteady state due to the existence of phase change material. The results from simulation exhibit the impact of phase change material installation, on outlet water, Pyrex and absorber temperature, thermal loss and thermal efficiency under various sun radiations. Furthermore the temperature and physical condition of PCM is roughly calculated through the system performance. In the end, according to the output of simulated systems and selection of suitable PCM there is possibility of reduction in thermal loss and system optimization.